Empowering Frontline Primary Healthcare Workers in a Global Health Partnership Training of Trainers Intervention to Strengthen the Prevention and Control of Cardiovascular Disease in Mozambique - Philippa Harris; Edna Juga; Neusa Bay; Chamila Adams; Patrícia Nhatitima; Adjine Mastala; Nilza Matavel; Arminda Mufanequisso; Nelta Mabote; Eunice Mondlane; Naisa Manafe; Paula Pinto; et al. (Ubiquity Press, 2022)
Background: Unpreparedness of health professionals to address non-communicable diseases (NCD) at peripheral health facilities is a critical health system challenge in Mozambique. To address this weakness and decentralize NCD care, training of the primary care workforce is needed. We describe our experience in the design and implementation of a cascade training of trainers (ToT) intervention to strengthen the prevention and control of cardiovascular disease. Methods: Between October 2018 and March 2020 a multidisciplinary global technical partnership was used to train frontline primary care health professionals from a resource-poor suburban setting in Maputo, Mozambique. Following engagement with local policy makers, clinicians, and academics, core training materials were developed, and a ToT cascade was implemented, supported by an on-site pilot clinic. Knowledge and confidence acquisition by participants and new local trainers were assessed using pre- and post-training surveys, while trainees and trainers completed further evaluation surveys at the end of the program. Results: Three ToT workshops trained 60 mixed cadre healthcare workers in assessment, diagnosis and management of hypertension, diabetes, and cardiovascular risk; of these, 11 became new local trainers. Mean pre- and post-test scores improved in all three training workshops (53% to 90%, 59% to 78%, and 58% to 74% respectively). New local trainers were highly rated by their trainees and reported increased confidence as trainers (mean Likert scale 3.0/5 pre-training to 4.8/5 post-training). Conclusion: This global health partnership delivered interprofessional training with good knowledge acquisition and increased self-reported confidence. Intensive local supervision and hands-on training empowered a new cohort of trainers to strengthen the prevention and control of cardiovascular disease and is likely to improve coordination and integration at primary care level as well as support the national scale up of NCD care delivery.